2014
DOI: 10.1021/nl502331f
|View full text |Cite
|
Sign up to set email alerts
|

Strong Sulfur Binding with Conducting Magnéli-Phase TinO2n–1 Nanomaterials for Improving Lithium–Sulfur Batteries

Abstract: Lithium-sulfur batteries show fascinating potential for advanced energy storage systems due to their high specific capacity, low-cost, and environmental benignity. However, the shuttle effect and the uncontrollable deposition of lithium sulfide species result in poor cycling performance and low Coulombic efficiency. Despite the recent success in trapping soluble polysulfides via porous matrix and chemical binding, the important mechanism of such controllable deposition of sulfur species has not been well under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
469
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 647 publications
(486 citation statements)
references
References 49 publications
(68 reference statements)
8
469
0
1
Order By: Relevance
“…Tao et al has also studied the Ti 4 O 7 material and provided understanding of LiPSs binding via DFT calculations. 56 Using the Ti 4 O 7 (1−20) surface as an test substrate, the optimized geometry indicated that the small sulfur clusters S x (x = 1,2,4) are preferentially bonded to low coordinated Ti sites.…”
Section: Polar-polar Chemical Interactions With Polysulfidesmentioning
confidence: 99%
“…Tao et al has also studied the Ti 4 O 7 material and provided understanding of LiPSs binding via DFT calculations. 56 Using the Ti 4 O 7 (1−20) surface as an test substrate, the optimized geometry indicated that the small sulfur clusters S x (x = 1,2,4) are preferentially bonded to low coordinated Ti sites.…”
Section: Polar-polar Chemical Interactions With Polysulfidesmentioning
confidence: 99%
“…25,59,60 Compared to the inorganic additives as reported in other studies, we demonstrated that polymer-based additives can also exhibit remarkable enhanced redox efficiency of the polysulfides. Poly(2,2,6,6-tetramethyl-1-piperidinyloxy-4-yl methacrylate) (PTMA), which is a stable free radical polymer reported to be potential organic electrode materials, 86 can behave as an efficient additive for high performance Li-S batteries once it was activated via in situ electrochemical oxidation (Fig.…”
Section: Polymer-based Functional Additives To Promote Polysulfide Rementioning
confidence: 51%
“…25,60 As subsequently reported by various other groups, the use of metal oxides, 2D metal carbides/carbonitrides, or doped carbon materials as sulfur hosts or functional additives can also help to suppresses the polysulfide shuttle and improve the polysulfide redox kinetics, often simultaneously. 21,[60][61][62][63][64][65][66][67][68][69][70][71] The downside of adding these inactive materials is the reduction in energy density of the final product the Li-S battery, and the requirement of high specific surface area of the these additives also brings the challenge of materials dispersibility in long and repeated cycles. Although there are still many obstacles to overcome, development of functional additives based on special surface chemistry will be beneficial for Li-S cathodes in the near future.…”
mentioning
confidence: 90%
“…[76][77][78] Nazar's group firstly reported that Ti 4 O 7 has a high affinity for lithium polysulphides due to the contained polar O-Ti-O units. 78 The presence of strong metal oxide-polysulfide interactions has been proved by X-ray photoelectron spectroscopy (XPS), X-ray absorption near-edge structure (XANES) and lithium polysulphides adsorption studies.…”
Section: Nanostructured Metal Oxides Application In Li-s Batteriesmentioning
confidence: 99%
“…Following on Cui's group reported that, compared with the TiO 2 -S, the Ti 4 O 7 -S cathodes exhibited a higher reversible capacity and improved cycling performance. 77 The superiorities of Ti 4 O 7 -S cathodes could be attributed to the strong adsorption of sulfur species on the low-coordinated Ti sites of Ti 4 O 7 , which was revealed by density functional theory (DFT).…”
Section: Nanostructured Metal Oxides Application In Li-s Batteriesmentioning
confidence: 99%